Contributions of Open Air Museums in preserving heritage buildings: study of open-air museums in South East England - Zuraini Md Ali; Rodiah Zawawi (Journal of Design and the Built Environment, 2010)
Most open air museums were established to preserve and present a threatened aspect of regional or national culture and to help forge a sense of identity and achievement. Britain's open air museums have aroused controversy among both museum professionals and building conservationists. They have been praised for spearheading innovative and vivacious approaches towards heritage interpretation and saving neglected buildings, while some have criticised them for inconsistent standards of conservation especially for taking buildings out of their original settings. Such architectural issues were strongly debated in the 1970s, while recent debates focus on popular approaches towards attracting the public to the past. This paper describes the evolution of open air museums in Britain, their contribution in conserving unloved buildings and how they have become an increasingly competitive tourist attraction. Observations and lessons learned from interviews and visit to two open air museums in South East England provides some insight about the importance of such museums. Operated as registered charity organisations, they have played significant roles not only in saving various buildings and structures from demolition but also in helping visitors to appreciate the rich heritage of these regions.